A Numerical Model for Heat and Moisture Transfer in Porous Media of Building Envelopes - Scussiato, T.; Ito, W. H.; Ramis, J.; Braga de Queiroz, P. I. (Engineering, Technology & Applied Science Research, 2022)
This study presents a one-dimensional quantitative analysis of unsaturated flow in natural stones using a numerical model (Finite Difference Method) and a mass balance for the heat flow. For that, we considered heat and moisture transfer between the external environment and a porous media (sandstone and limestone) with homogeneous characteristics. For unsaturated water flow, Richards’ equation and the formulation proposed by Gardner for volumetric water content and hydraulic conductivity were considered. The results of the numerical analysis showed that the evaporation of porewater throughout summer days (January 3rd and 4th) considerably reduced the temperature of the roof by about 8°C. The accumulated conductive heat flow and the volumetric water content were also reduced due to the evaporation process. This fact indicates that evaporation can be useful in providing thermal comfort and, consequently, in improving the energy efficiency of buildings with natural stones as envelopes.